2002
DOI: 10.1007/s00464-002-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic gatrojejunostomy for palliation of gastric outlet obstruction in unresectable gastric cancer

Abstract: Laparoscopic GJ for the palliation of unresectable advanced gastric cancer can achieve excellent results with less suppression of immune function, lower morbidity, greater improvement of hemodynamic activities, and earlier recovery of bowel movements than OGJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
56
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 19 publications
4
56
0
4
Order By: Relevance
“…Nine articles met the eligibility requirements and were included in the review (Fig. 1) [12][13][14][15][16][17][18][19][20]. All included articles were retrospective, single-institution case series, except for one [19] that included a prospective collection of patient-reported outcomes for a subset of patients using a questionnaire ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine articles met the eligibility requirements and were included in the review (Fig. 1) [12][13][14][15][16][17][18][19][20]. All included articles were retrospective, single-institution case series, except for one [19] that included a prospective collection of patient-reported outcomes for a subset of patients using a questionnaire ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported specifically the absence of symptoms in 13.2% of non-curatively managed patients [13]. An additional 3 of the 9 studies reported that all patients had unresectable, symptomatic gastric outlet obstruction (GOO) requiring palliation [14][15][16].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations